2002
DOI: 10.1002/app.10496
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensionally braided carbon fiber–epoxy composites, a new type of materials for osteosynthesis devices. II. Influence of fiber surface treatment

Abstract: ABSTRACT:Interfacial adhesion between carbon fiber and epoxy resin plays an important role in determining performance of carbon-epoxy composites. The objective of this research is to determine the effect of fiber surface treatment (oxidization in air) on the mechanical properties (flexural strength and modulus, shear and impact strengths) of three-dimensionally (3D) braided carbon-fiber-reinforced epoxy (C 3D /EP) composites. Carbon fibers were air-treated under various conditions to improve fiber-matrix adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Under a treatment temperature of 450°C the surface does not look appreciably different when compared to untreated ones, which suggests that the treatment was mild and did not cause essential morphological changes on the fibre surface [14]. However, by using the gas physical adsorption technique, Wan et al [11] reported that after treatment under a similar condition mentioned above, the total carbon fibre surface area was doubled. Their result indicated that some changes did take place on carbon fibre surface at 450°C, although it was difficult to be recognized by SEM.…”
Section: Sem Observationmentioning
confidence: 88%
See 1 more Smart Citation
“…Under a treatment temperature of 450°C the surface does not look appreciably different when compared to untreated ones, which suggests that the treatment was mild and did not cause essential morphological changes on the fibre surface [14]. However, by using the gas physical adsorption technique, Wan et al [11] reported that after treatment under a similar condition mentioned above, the total carbon fibre surface area was doubled. Their result indicated that some changes did take place on carbon fibre surface at 450°C, although it was difficult to be recognized by SEM.…”
Section: Sem Observationmentioning
confidence: 88%
“…Oxidation treatment of carbon fibres in hot air is one of the commonly used approaches owing to several advantages, e.g. easy operation, low cost and lack of pollution [11]. On the other hand, cryogenic treatment of carbon fibres, which could increase the fibre strength by clearing the weak layer of amorphous carbon, seems to be an interesting and relatively novel method.…”
Section: Introductionmentioning
confidence: 99%
“…When these modified GFs are applied in the epoxy matrix, the 'rough' surface of the GF makes the mechanical interlocking between the GF and the epoxy matrix much more pronounced. As studied by other researchers [27,28,31,32,37,38], this mechanical interlocking at the fiber-matrix interface helps to enhance the fiberÀmatrix bond and improves the flexural and shear properties of the composites. Greater work must be done to deform or shear the samples when the fiberÀmatrix bond is improved in this manner.…”
Section: Silica Modified Gf Reinforced Compositementioning
confidence: 91%
“…Therefore, it can be concluded that although micro-pits formed on fiber surfaces may strengthen fiber-matrix bond, higher exposure may cause great loss of fiber strength. Therefore, a trade-off between the fiber-matrix bond and fiber strength loss should be considered [40]. Placing fibers in the resin toughens the composite through different mechanisms among them are blunting the crack front path or changing the crack direction [41].…”
Section: Discussionmentioning
confidence: 99%